2021
DOI: 10.3390/toxics9110299
|View full text |Cite
|
Sign up to set email alerts
|

Female Reproductive Health and Exposure to Phthalates and Bisphenol A: A Cross Sectional Study

Abstract: The xenoestrogenicity of some plasticisers (phthalates and bisphenol A) is documented in the literature and may pose a risk to female reproductive health. The aim of this study was to assess exposure to six phthalates. This was achieved by measuring their respective metabolites (mono-ethylphthalate (MEP); mono-n-butylphthalate (MnBP); mono-n-ottylphthalate (MnOP); and monobenzylphthalate (MBzP)), as well as the sum of two of the diethyl-hexyl phthalate metabolites-(∑DEHP) and bisphenol A (BPA) in a female popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…ΣDBP and ΣDEHP have been shown to inhibit regular activity of T3 [ 38 ], which could affect weight gain because phthalates disrupt the thyroid hormone system. Another study found that females with infertility, recurrent miscarriages, and tubal factors of endocrine dysfunction had higher ∑DEHP concentrations [ 39 ]. The results of this study differ from those of previous studies, which indicated that in premenopausal women, the strongest association was with higher concentrations of MBzP [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…ΣDBP and ΣDEHP have been shown to inhibit regular activity of T3 [ 38 ], which could affect weight gain because phthalates disrupt the thyroid hormone system. Another study found that females with infertility, recurrent miscarriages, and tubal factors of endocrine dysfunction had higher ∑DEHP concentrations [ 39 ]. The results of this study differ from those of previous studies, which indicated that in premenopausal women, the strongest association was with higher concentrations of MBzP [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, women are more likely to be exposed to phthalates than men. This could be linked to the more frequent use of cosmetics and personal care products by women compared to men [ 17 , 18 , 19 ]. Exposure to phthalates and their metabolites can interfere with ovarian function by targeting both folliculogenesis and steroidogenesis.…”
Section: Phthalatesmentioning
confidence: 99%
“…MEHP is known to cause metabolic disorders, endocrine disruption, and development and reproductive impairments in humans and other species [ 57 , 85 , 86 , 87 , 88 , 89 , 90 ]. DEHP is rapidly metabolized, both in invertebrates and vertebrates, in its primary metabolite, MEHP [ 91 ].…”
Section: Resultsmentioning
confidence: 99%